Design of a Web-Based Point of Sale System for Warung Bakso Megaria - Anggara, Ariski Try; Sudarmilah, Endah (Journal La Multiapp, 2025)
Warung Bakso Megaria, like many other eateries, still relies on manual transaction processes that are prone to errors and time-consuming. This can hinder operational efficiency and customer experience. To address these issues and enhance competitiveness in the digital era, this study aims to design an integrated POS system for Warung Bakso Megaria. The POS system designed in this study offers several advantages: improving operational efficiency, minimizing errors, enhancing customer experience, providing accurate sales data, and increasing competitiveness.The study employs the Waterfall method from the System Development Life Cycle (SDLC) as its framework. The POS system is designed considering the needs and scale of Warung Bakso Megaria's business. System testing was conducted using the blackbox method and the System Usability Scale. The outcome of this research is an information system that has undergone two stages of testing. The first test used the blackbox method to validate features through input and output processes, yielding valid results in ten tests. The second test employed the System Usability Scale, achieving a score of 70, which falls into the "Good" category (scale 68-80) and is deemed acceptable.